2007
DOI: 10.1002/ijc.22509
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and tea consumption and risk of hepatocellular carcinoma in Italy

Abstract: The role of coffee in the aetiology of hepatocellular carcinoma has raised great interest. In Italy, coffee consumption is high, thus allowing the investigation of the topic over a broad range of consumption. A hospital-based case-control study was conducted in Italy in [1999][2000][2001][2002], including 185 incidents, histologically confirmed cases of hepatocellular carcinoma aged 43-84 years. Controls were 412 subjects admitted to the same hospitals' networks for acute, non-neoplastic diseases unrelated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
79
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 35 publications
4
79
1
1
Order By: Relevance
“…Our results from this prospective cohort study support the findings in some (Gelatti et al, 2005;Ohfuji et al, 2006), although not all (Montella et al, 2007), case-control studies that suggested a protective effect of coffee among HCV-positive individuals. Some patients with hepatitis or liver cirrhosis, however, may have decreased coffee consumption at their physician's advice or due to impaired caffeine metabolism in the liver (Hasegawa et al, 1989).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results from this prospective cohort study support the findings in some (Gelatti et al, 2005;Ohfuji et al, 2006), although not all (Montella et al, 2007), case-control studies that suggested a protective effect of coffee among HCV-positive individuals. Some patients with hepatitis or liver cirrhosis, however, may have decreased coffee consumption at their physician's advice or due to impaired caffeine metabolism in the liver (Hasegawa et al, 1989).…”
Section: Discussionsupporting
confidence: 90%
“…The inverse associations between coffee consumption and the risk of hepatocellular carcinoma (HCC) have recently been reported not only from case -control studies (Gallus et al, 2002;Gelatti et al, 2005;Ohfuji et al, 2006;Montella et al, 2007;Tanaka et al, 2007) but also from Japanese cohort studies (Inoue et al, 2005;Kurozawa et al, 2005;Shimazu et al, 2005). Cohort studies are superior to case -control studies in avoiding recall and selection bias (Ohfuji et al, 2006).…”
mentioning
confidence: 99%
“…In a recent meta-analysis, 8 including all indicated studies, as well as three studies reporting statistically nonsignificant inverse 19,26 or null 27 associations, the summary relative risk for HCC for any versus no coffee consumption was 0.60 (95% CI, 0.50-0.71), with a dose-response trend. With the exception of one Italian case-control study, 25 studies on tea consumption and HCC risk have been conducted exclusively in Asia (where green tea consumption is more frequent than in Europe); the results are collectively inconclusive. Two studies reported statistically significant inverse associations, 28,29 four inverse but statistically nonsignificant associations, [30][31][32][33] two null associations, 19,34 whereas three reported positive, albeit statistically nonsignificant associations.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported statistically significant inverse associations, 28,29 four inverse but statistically nonsignificant associations, [30][31][32][33] two null associations, 19,34 whereas three reported positive, albeit statistically nonsignificant associations. 17,25,35 A meta-analysis of these studies 9 pointed to a suggestive inverse association of tea with primary liver cancer. Our study, the first cohort study outside Asia, indicates an inverse, dose-dependent association of tea with HCC risk, which is not incompatible with the results of the indicated meta-analysis, although our findings point to a stronger inverse association.…”
Section: Discussionmentioning
confidence: 99%
“…Outside Asia, three studies investigated the role of tea on liver cancer (11)(12)(13). They were conducted among European populations, where the tea-drinking culture is less frequent and black rather than green tea is usually consumed.…”
mentioning
confidence: 99%